2018
DOI: 10.1186/s12886-018-0811-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between glaucoma and risk of depression: a nationwide population-based cohort study

Abstract: BackgroundPrevious cross-sectional studies revealed a higher prevalence of depression among glaucoma patients. However, cohort studies were in lack to build the risk of incident depression after the diagnosis of glaucoma. The aim of our study was to investigate the association between glaucoma and the subsequent risk of developing depression and to assess risk factors associated with depression in glaucoma patients.MethodsA population-based retrospective cohort study using the Taiwan National Health Insurance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
1
34
0
5
Order By: Relevance
“…secondary glaucoma and the results were not adjusted for type of glaucoma. A large populationbased study assessed depressive symptoms in persons with or without self-reported glaucoma and found no differences between the two groups [19]. Again, the study did not assess the severity or subtype of glaucoma and was performed in a population-based sample why both persons with severe depression and advanced glaucoma may have evaded participation.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…secondary glaucoma and the results were not adjusted for type of glaucoma. A large populationbased study assessed depressive symptoms in persons with or without self-reported glaucoma and found no differences between the two groups [19]. Again, the study did not assess the severity or subtype of glaucoma and was performed in a population-based sample why both persons with severe depression and advanced glaucoma may have evaded participation.…”
Section: Plos Onementioning
confidence: 99%
“…Most of the evidence for attenuations in the NIF physiologic responses to light is based on studies in primary open angle glaucoma [12,14,15,17]. The majority of studies assessing sleep and mood alterations were however performed in heterogenous populations of patients with both primary and secondary glaucomatous disease [8,9,11,19,20]. There is a lack of knowledge of how NIF functions are affected in different subtypes of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Для исследования взаимосвязи глаукомы и возможности последующего развития депрессии было проведено ретроспективное когортное исследование населения Тайваня с использованием базы данных Тайваньского национального центра медицинского страхования [13,14]. В исследование вошло 8777 пациентов с глаукомой и 35 108 здоровых лиц.…”
Section: Modern Multicenter Studies Of Psychological Features Proper unclassified
“…Кривые Каплана -Майера уровня депрессии у пациентов с глаукомой и контрольной группы. Черная линия представляет группу глаукомы, а серая -контрольную группу [13] Figure. Kaplan -Meier curves of the level of depression in patients with glaucoma and the control group.…”
Section: Modern Multicenter Studies Of Psychological Features Proper unclassified
See 1 more Smart Citation